PEMANFAATAN DAN CARA MERACIK HERBAL TUMBUHAN OBAT ANTIDIABETES DAUN AFRIKA (Vernona amygdalina DELILE) DI KABUPATEN KEEROM PAPUA - Linus Yhani Chrystomo; I Made Budi; Aditya Krishar Karim (JURNAL PENGABDIAN PAPUA, 2018)
Community service with the title: Utilization and how to formulate medicinal plant of African leaf (Vernonia amygdalina Delile) in Keerom Papua, aims to provide the skills of Arsopura Village community in Skamto District of Keerom Regency.  The aims to this activities is the use and how to formulate antidiabetic medicinal plants.  Diabetes mellitus is a disease caused due to metabolic disorders of the body, where the sugar content in the body can not be catalyzed by the enzyme insulin which was produced the pancreas gland. Herbal antidiabetes formulated from African leaf plants is a traditional knowledge based on local wisdom Kerom community hereditary used to cure diabetes melitus diseases. This activities is an effort to raise the local wisdom  about traditional medicine that has been empirically or hereditary has been used as a traditional medicine antidiabetes. Utilization of herbs of traditional medicinal plants need to be socialized by providing skills how to use it and how to formulate to local communities in the Arsopura Village, Keerom regency according to the guidelines regulation of the Supervision of Food and Drug Indonesian Government  about the Making of Good Traditional Drugs (CPOTB). According to Institution of Supervision of Food and Drug Indonesian Government  that traditional medicine has been used for from generation to generation can be used by the community without having to get permission from The Institution of Supervision of Food and Drug Indonesian Government. Traditional medicine must also have the criteria of safety, quality and efficacy. The purpose of this activities is to provide knowledge on how to utilize and skill how to use herbs of traditional African antidiabetes leaf medicine in Keerom Regency. The method of education used is the lecture or extension method of herbal medicine utilization of traditional antidiabetic medicinal plants, how to use and how to cultivate it. The result data of this activities can be concluded that local people in Arsopura Village, Keerom Regency are very enthusiastic to study the utilization of traditional antidiabetes leaf medicinal plants of Africa and how to mix herbs of traditional antidiabetic medicinal plants and how to cultivate them as Medicinal Plants for family (TOGA). The answer of the question post increasingly and extends to various diseases and herbs that can be used to other disease. Suggestions need assistance in mixing herbs traditional antidiabetes medicinal plants and how to cultivate these plants.Keywords: Herbs, antidiabetes, Vernonia amygdalina,  diabetes mellitus, Keerom